The effect of irrigation by domestic waste water on soil properties (International Journal of Irrigation and Water Management, 2016)
To investigate the beneficial impacts of domestic waste water on soil properties, we conducted an experiment in the lysimeter by measuring certain features essentially related to soil characteristics. The objectives in this study were (i) the domestic waste water in filtration by soil and (ii) the effect of domestic waste water on soil properties. In this experiment, we had 15 lysimeters that 1 - 5 lysimeters were irrigated by domestic waste water and primary drainage water was accumulated from these lysimeters and 6 - 9 lysimeters were irrigated by primary drainage water and secondary drainage water was accumulated and 10, 11 and 12 lysimeters were irrigated by secondary drainage water. In order to compare soil properties, 13, 14 and 15 lysimeters were irrigated by agronomical water and finally, soil and water properties were analyzed in each stage. The results showed that, soil could filter the domestic waste water and reduced BOD5 and COD of domestic waste water. Also, irrigation with domestic waste water increased nutritive elements in soil that can be source of nutrition for plants. The findings may give applicable advice to commercial farmers and agricultural researchers for management and proper use of water.